Assessment of Mangrove Ecosystem Potency and Its Utilization in Dompu Regency Coastal Waters, West Nusa Tenggara Province Using Satellite Imagery Application - Yulius Yulius; Syahrial Nur Amri; August Daulat; Sari Indriani Putri (Pusat Riset Kelautan, 2019)
Mangrove ecosystem forests are tropical coastal vegetation communities, which has the ability to grow in coastal area with tidal and muddy environment. Several functions of mangrove ecosystem forest such as ecological functions can be used for coastal protection, trapping sediment and strengthen the coastal ecosystems. Coastal waters in Dompu Regency, West Nusa Tenggara have natural mangrove ecosystem with a huge potency and advantages to the region. This study aimed to understand the condition of mangrove ecosystem based on satellite image analysis of Landsat 8 Operational Land Imager (OLI) in 2014 and assess the potency, information related to the utilization by community. Data collection in this study were combined from satellite imagery interpretation with interview and questionnaires. The results showed that the mangrove forest extent in Dompu Regency Coastal Waters were about 90,631 ha with uniformity index 0.68 (medium uniformity). Two mangrove species were found in the region namely Rhizopora stylosa and Rhizopora apiculata and used by the community for several purposes such as firewood, natural coastal protection from tidal, waves and abrasion, also for crabs and fish spawning ground.